The role and importance of digitalization in the activities of the prosecutor’s office to protect the rights of entrepreneurs - Kalmaganbetova, D.B.; Smatlaev, B.M.; Kussainova, L.K. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2013)
The article examines the issues of introducing digital technologies into the activities of the prosecutor’s office to protect the rights of entrepreneurs. In connection with the impact of innovative development, the transformation of the public space of all spheres of social life is taking place, which is based on the rapid development of the digitalization process. Digital technologies have proven to be a key part of the solution during the crisis, allowing governments to continue providing essential social services, enabling many businesses to continue their operations and keeping people connected. The potential of digital technologies as a transformative force for nations is clear, as is the commitment to bridging the digital divide. The team of authors analyzes current problems and prospects for organizing prosecutorial activities in the context of digitalization. The interaction and integration within formation systems of other state bodies and their role in the implementation the entire process of digitalization and the protection of the rights of entrepreneurs.